(untitled) (Research, Society and Development, 2020)
Computer-assisted semen analysis (CASA) systems have been one the most used tools to evaluate sperm kinetics. The objective of this research was to estimate the correlation between sperm motility characteristics evaluated by CASA during 72 hours of cooling with the farrowing rate (FR) and total number of piglets born (TNB) after artificial insemination. Multiparous sows (n=464) were inseminated with semen from seven boars (19.6 ± 1.3 ejaculates/male). Sperm motility parameters were determined immediately after dilution and after 24, 48 and 72 hours of cooling at 15°C: total motility (TM-%), progressive motility (PM-%), curvilinear velocity (VCL-μm/s), straight line velocity (VSL-μm/s), average path velocity (VAP-µm/s), amplitude of lateral head displacement (ALH-µm), flagellar beat cross frequency (BCF-Hz), straightness (STR-%) and linearity (LIN-%). Pearson’s correlation coefficient was applied to analyze the data and the comparison of the means of the sperm characteristics between the boars was done by Tukey’s test at 5% probability. TM and PM at time zero (T0) were significant and had a moderate to high correlation with FR and TNB. After 72 hours of refrigeration, the semen quality was reduced and showed a significant and low correlation of the TM and PM with these same parameters. The boar presenting the lowest value of TM and PM after dilution obtained lower FR and TNB. In conclusion, computer-assisted semen analysis soon after dilution can be used to predict fertility of boars.